PERBEDAAN PENGETAHUAN CARA MENYIKAT GIGI SEBELUM DAN SESUDAH DILAKUKAN PENYULUHAN DENGAN MEDIA RODA PUTAR (Roulatte) PADA SISWA MTsN 3 HULU SUNGAI TENGAH - Raudatul Septia Anggraini; Waljuni Astu Rahman; Naning Kisworo Utami (JURNAL TERAPIS GIGI DAN MULUT, 2021)
The national prevalence of dental and oral problems is 25.9%. In fact, in the teeth, it was found that most of the Indonesian population's dental behavior during bathing in the morning and evening showers was 76.6%. And those who teeth properly after eating and before going to bed at night for Indonesians were found to be 2.3%. Through outreach programs, they can increase knowledge and awareness of the importance of maintaining dental and oral health and can actively participate in improving self-care efforts. In addition, with counseling, a person can work himself in an effort to prevent teeth and mouth This study aims to determine the difference in knowledge of how to teeth before and before counseling with a swivel wheel (roulette). The research design used is "One Group Pretest-Posttest". The research population found 223 people and the research sample found 49 people, the sampling technique used purposive sampling with the Wilcoxon test. Research on dental knowledge before and before the test was carried out with counseling using roulette with the average value obtained before counseling was 5.31 and before counseling was 8.86. Based on the Wilcoxon test, the Asymp value was obtained. Signature. (2-tailed) 0.000 with a = 0.05 so that p < a. The conclusion of the study was that there was a difference in knowledge of dental procedures before and before counseling with media was carried out on students at MTsN 3 Hulu Sungai Tengah. It is recommended to use effective counseling with this rotating media because it increases dental knowledge in students. Keywords: Knowledge, Dental Media Method, Counseling, Spin Wheel